Studies on the Degree of Soil Fertility Impoverishment under Different Plantation Crops in Little Andaman - Narayan, Lalit; Ghoshal Chaudhuri, S.; Muralidhar Rao, Ch. (Indian Forester, 1998)
Studies were carried out in the plantations of the Andaman&Nicobar Islands Forest and Plantation Development Corporation Ltd. in Little Andaman to ascertain the fertility status under different plantation crops along with different annual crop sequences in order to know the rate of fertility impoverishment of soils in comparison to the original forest floor. This study throws light on the faster degree of impoverishment crept in the original build up of rich tropical forest floor. The impoverishment is found to be slower in case of crop rotation with nitrogen fixing legumes in cereal crops as well as deciduous crops such as Cashew.